2021
DOI: 10.1007/s42484-020-00035-5
|View full text |Cite
|
Sign up to set email alerts
|

Facial expression recognition on a quantum computer

Abstract: We address the problem of facial expression recognition and show a possible solution using a quantum machine learning approach. In order to define an efficient classifier for a given dataset, our approach substantially exploits quantum interference. By representing face expressions via graphs, we define a classifier as a quantum circuit that manipulates the graphs adjacency matrices encoded into the amplitudes of some appropriately defined quantum states. We discuss the accuracy of the quantum classifier evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Graph theory may best encode the human face and can be used to identify facial expressions. Quantum computing has recently tried to address the problem of graph classification for emotions like happy or sad using facial expressions [65]. The proposed research primarily intends to quantify the intensities related to happy and sad emotions using a quantum computer, This research intends to address the future scope of [65] by including a variational algorithm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graph theory may best encode the human face and can be used to identify facial expressions. Quantum computing has recently tried to address the problem of graph classification for emotions like happy or sad using facial expressions [65]. The proposed research primarily intends to quantify the intensities related to happy and sad emotions using a quantum computer, This research intends to address the future scope of [65] by including a variational algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Quantum computing has recently tried to address the problem of graph classification for emotions like happy or sad using facial expressions [65]. The proposed research primarily intends to quantify the intensities related to happy and sad emotions using a quantum computer, This research intends to address the future scope of [65] by including a variational algorithm. The proposed variational algorithm established the intensity of the identified emotions with the help of quantum circuits.…”
Section: Methodsmentioning
confidence: 99%
“…The model by Mengoni et al [20] utilizes Schuld et al's [5] quantum interference circuit for classifying facial expressions. However, Mengoni et al [20] identified the closest match by evaluating the distance between a test instance and a random instance from each training batch. Hence, representative selection becomes crucial for the model.…”
Section: Related Workmentioning
confidence: 99%
“…Figure 4 shows the third component of the feature vector f k= (2,4,6,8),nmax=8 for all the 75 embeddable graphs, calculated by three methods:…”
Section: Feature Vectors Comparisonmentioning
confidence: 99%
“…At the same time, improvements on graph neural networks [6] show that graph isomorphism plays a central role in the classification itself. The emergence of their quantum counterparts [7] with already proven applications [8] motivated us to investigate how photonics chips could help in this field. A preliminary part of our study was to determine to which extent graphs can be embedded on a photonic device and how one can derive isomorphism properties from it.…”
Section: Introductionmentioning
confidence: 99%